Facetten van Jonge Limburgse Kunst. - Van Bergen, Johan; Provinciaal Begijnhof, Hasselt (Hasselt : Culturele Dienst van de Provincie Limburg, 1970)
Beets, Lowie ; Brouwers, Rob ; Ceyssens, Sylvain ; Coolen, Rik ; Cuppens, Thea ; Daniëls, Albert ; De Roy, Ida ; Dumont, Thérèse ; Segers, Gerard ; Stockmans, Piet ; Swartenbroeckx, Guido ; Van den Broeck, Téjo ; Vanoverbeke, Carly ; Van Straelen, Erik ; Van Vickenroye, Stan ; Wijckmans, Marie-Rose ; Withofs, Jan ; Wauters, Paul ; Zeegers, Ludo ; Francis, Maggy ; Hermens, Bert ; Hoewaer, Lidy ; Jacobs, Jos ; Keil, Hélène ; Kumpen, Marcel ; Mathijs, André ; Mommen, Joris ; Mulkers, Urbain ; Pottharst, Bärbel ; Ramman, Francq
Facetten van Jonge Limburgse Kunst, Provinciaal Begijnhof, Hasselt, 14-2 - 8.3-1970
boek
Keywords: Limburg